2015
DOI: 10.1007/s10278-015-9803-7
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Dimensional Accuracy of 3-D Printed Anatomical Structures Derived from CT Data

Abstract: Additive manufacturing and bio-printing, with the potential for direct fabrication of complex patient-specific anatomies derived from medical scan data, are having an ever-increasing impact on the practice of medicine. Anatomic structures are typically derived from CT or MRI scans, and there are multiple steps in the model derivation process that influence the geometric accuracy of the printed constructs. In this work, we compare the dimensional accuracy of 3-D printed constructs of an L1 vertebra derived from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(38 citation statements)
references
References 18 publications
1
35
0
Order By: Relevance
“…Motion artifacts introduced during image acquisition affects the subsequent extraction of region of interest [30]. It is challenging to separate cardiac tissues from the adjacent tissues of similar Hounsfield units.…”
Section: Can a Static Cardiac Model Represent A Real Dynamic Heart?mentioning
confidence: 99%
“…Motion artifacts introduced during image acquisition affects the subsequent extraction of region of interest [30]. It is challenging to separate cardiac tissues from the adjacent tissues of similar Hounsfield units.…”
Section: Can a Static Cardiac Model Represent A Real Dynamic Heart?mentioning
confidence: 99%
“…Salmi et al noted a mean error in selective layer sintering models of 0.79 and 0.80 mm, whilst McMenamin et al identified a mean error of 0.53 mm in a material jetting model. Some substantial replication error has been noted in previous studies, as indicated by the measurement error ranging from 0.8 to 1.5 mm noted in models analysed by Ogden et al…”
Section: Discussionmentioning
confidence: 74%
“…Poor segmentation can be a significant source of error introduction, and the choice of automatic threshold value and technique of manual segmentation to isolate anatomy have all been proven to have an effect on replication accuracy . George et al have indicated that poor segmentation can introduce error reaching up to 4 mm.…”
Section: Discussionmentioning
confidence: 99%
“…Establishing accuracy will be more difficult than establishing reproducibility however, as there is limited opportunity to compare a printed model with the true patient anatomy. Cadaveric studies have been described [3638] wherein printed models were compared to autopsy findings. Another opportunity is to compare the dimensions of tissue excised or visualized at surgery with those of the model [13], but the former depends on the completeness of excision and the latter is limited to areas/surfaces of tissues exposed in the surgical field as well as accurate measurement calibration that is often limited by the degree of access.…”
Section: Imaging Considerationsmentioning
confidence: 99%
“…Vertebral bodies can be printed accurately and reproducibly from non-contrast CT with minimal segmentation effort [38, 73] given the high tissue-bone contrast, and their utility in corrective surgery is rapidly being assessed. A large-scale study in 126 adolescent idiopathic scoliosis patients used 3D printed models of the entire spine to plan the corrective procedure, identifying complex or abnormal structures and simulating screw implantation.…”
Section: Thoracic Applicationsmentioning
confidence: 99%